ADSORPTION OF ORGANIC COMPOUNDS AND HAZARDOUS MICROORGANISMS FROM SEWAGE AND SURFACTANT-CONTAINING WASTEWATER USING CARBON-BASED NANOMATERIALS: A FOCUS ON GRAPHENE OXIDE AND CARBON NANOTUBE - YOUNAS , A; RASHAD , M; RAFAQAT , A; MAQBOOL , H; GUL , K; AHMAD , M; SHAHBAZ , J; KANWAL , KU; UMAIR , M (Biological and Clinical Sciences Research Journal, 2024)
This review comprehensively examines the utilization of carbon-based nanomaterials, specifically graphene oxide (GO) and carbon nanotubes (CNTs), in advanced wastewater treatment applications. GO and CNTs demonstrate exceptional efficacy in adsorbing a broad spectrum of organic compounds and hazardous microorganisms due to their unique physicochemical properties, such as large specific surface areas, high aspect ratios, and versatile chemical modifications enabled by functional groups. GO is characterised by abundant oxygen-containing groups, including hydroxyl, carboxyl, and epoxy, which enhance its hydrophilicity and adsorption potential for cationic pollutants. Meanwhile, CNTs, available as single-walled (SWCNTs) and multi-walled (MWCNTs), are noted for their tubular structure, high tensile strength, and significant electrical conductivity, making them highly effective in adsorbing organic molecules and heavy metals. The review explores the mechanisms of action of these nanomaterials, which encompass physical adsorption through van der Waals forces and π-π interactions, as well as chemical adsorption involving covalent or ionic bond formation with contaminants. Recent innovations in hybrid systems that integrate GO and CNTs with other technologies, such as photocatalysis and membrane filtration, are highlighted for enhancing contaminant removal and energy efficiency in water purification processes. The review addresses critical challenges related to nanoparticle stability, recovery, production costs, and the environmental and health impacts of deploying these nanomaterials in practical applications. Crucial issues, such as nanoparticle aggregation, reusability, and the safe disposal of used materials, are identified, with potential solutions including surface modifications to improve dispersion and the incorporation of magnetic nanoparticles for easier recovery. The findings emphasise the significant potential of GO and CNTs in advancing environmental remediation technologies, offering promising avenues for developing cleaner and more efficient water treatment solutions. As the field progresses, the continued exploration and interdisciplinary collaboration promise substantial water purification and environmental protection advancements.